Clinical Outcomes Associated With Respiratory Virus Detection Before Allogeneic Hematopoietic Stem Cell Transplant - Campbell, Angela P. (Clin Infect Dis, 2015)
Background. The management of respiratory virus infections prior to hematopoietic cell transplant (HCT) is difficult. We examined whether respiratory virus detection before HCT influenced the requirement for bronchoscopy, hospitalization, and overall survival following HCT. Methods. Pre-HCT and weekly post-HCT nasal washes were collected through day 100 from patients with and without symptoms. Samples were tested by multiplex polymerase chain reaction for respiratory syncytial virus, parainfluenza viruses 1–4, influenza A and B, human metapneumovirus, adenovirus, and human rhinoviruses, coronaviruses, and bocavirus. Results. Of 458 patients, 116 (25%) had respiratory viruses detected pre-HCT. Overall, patients with viruses detected pre-HCT had fewer days alive and out of the hospital and lower survival at day 100 (adjusted hazard ratio [aHR], 2.4; 95% confidence interval [CI], 1.3–4.5; P = .007) than patients with negative samples; this risk was also present with rhinovirus alone (aHR for mortality, 2.6; 95% CI, 1.2–5.5; P = .01). No difference in bronchoscopy incidence was seen in patients with and without respiratory viruses (aHR, 1.3; 95% CI, .8–2.0; P = .32). In symptomatic patients, those with respiratory viruses detected had increased overall mortality compared with patients without viruses detected (unadjusted HR, 3.5; 95% CI, 1.0–12.1; P = .05); among asymptomatic patients, detection of respiratory viruses was not associated with increased mortality. Conclusions. These data support routine testing for respiratory viruses among symptomatic patients before HCT, and delay of transplant with virus detection when feasible, even for detection of rhinovirus alone. Further study is needed to address whether asymptomatic patients should undergo screening for respiratory virus detection before HCT.